Internationalization Plan - How can UniPlaces improve its customer acquisition strategy in the London market? - Gonçalves, Carla Alexandra Magalhães (2017)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics